Effect of Saponin from Tupistra chinensis Baker on proliferation and apoptosis of ovarian cancer cells by Wnt/β‐Catenin pathway. Issue 8 (5th June 2020) - Ji, Xiaoli; Yang, Chengcheng; Xie, Jia; Yin, Xiaolan; Hu, Quan
Abstract: The present study aimed to investigate the molecular mechanism and the effect of Saponin from Tupistra chinensis Baker (STCB) on the proliferation and apoptosis of ovarian cancer cells. To investigate the inhibitory effect of STCB on the proliferation of ovarian cancer cells, SKOV3 cells were cultured and the methyl thiazolyl tetrazolium assay was used. Flow cytometry was also used to analyze the cell cycle distribution and apoptotic rate. Ki‐67, cyclin D1, cleaved caspase‐3, cleaved caspase‐9, β‐catenin, and c‐Myc protein expressions were detected by western blot. Ovarian cancer cells were treated with STCB and Wnt pathway activator lithium chloride (LiCl). These methods were also used to determine the proliferation, cell cycle distribution, and apoptosis of ovarian cancer cells. In STCB‐treated group, the proliferation inhibition and apoptosis rate, the proportion of G0‐G1 phase, and the expression level of cleaved caspase‐3 and 9 of ovarian cancer cells were significantly increased. Similarly, the expression of Ki‐67, cyclin D1, β‐catenin, and c‐Myc were significantly decreased ( p < .05). The results also showed that in STCB‐LiCl‐treated group, while the proliferation inhibition rate of ovarian cancer cells, the proportion of G0‐G1 cells, the expression level of cleaved caspase‐3 and 9, and the apoptosis rate ( p < .05) were significantly decreased, the expression level of Ki‐67, cyclin D1, β‐catenin, and c‐Myc was significantly increased. STCB induced G0‐G1 phase arrest, inhibited cell proliferation, and promoted apoptosis of ovarian cancer cells by inhibiting Wnt/β‐catenin pathway.